Research on the resource development system and optimization Odel of urban football movement development - Hua, Ming; Yang, Kuikui; Gong, Yuanjun (Cambridge Sport Science, 2024)
The development of urban football is constrained by the available urban resource factors, and the development and optimization of urban football development resources are of great significance. The urban football resource development system includes tangible and intangible resources. The former can be developed in terms of venue resources, human resources, population resources, financial resources, and natural resources. The latter can be developed in terms of historical resources, cultural resources, institutional resources, network and media resources, and event resources. The optimization of football development resources can reduce constraints between resources and increase coordination and promotion. Optimization models can be explored both within and between categories of tangible and intangible resources.